Flood Risk Assessment of Public Infrastructure in Semarang City from an Insurance Perspective - Dita Mentari Putri; Hanggoro Iskandar Putra Wijaya; Tri Susanto (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Flooding poses a significant threat to public infrastructure, including facilities in Semarang. These risks can be transferred to third parties through insurance mechanisms. This study aims to assess vulnerability, exposure, and hazard levels as key components of flood risk assessment for public infrastructure from an insurance perspective. Primary data were collected through interviews and questionnaires with school and community health center infrastructure users, as well as insurance-related stakeholders. Secondary data were obtained from government agencies responsible for disaster management and infrastructure planning. The results show that 8.9% of infrastructure was classified as highly vulnerable, 42.2% as having medium vulnerability, and 48.9% as having low vulnerability. Exposure analysis indicated that 8.9% of infrastructure sustained severe damage, 68.9% sustained moderate damage, and 22.2% minor or no damage. Hazard analysis revealed that 46.7% of the infrastructure was located in high-hazard zones, 40% in medium-hazard zones, and 13.3% in low-hazard zones. Risk assessment findings indicate that 64.4% of the infrastructure falls into the low-risk category, 35.6% into the medium-risk category, and none into the high-risk category. The study highlights that implementing a risk-based insurance premium policy allows insurance rates to reflect the flood risk associated with each infrastructure asset more precisely, thereby promoting a more equitable distribution of insurance costs. However, the lack of stakeholder coordination remains a major challenge, as many stakeholders are unaware that public infrastructure is already insured. Improving coordination and awareness is essential for advancing flood insurance implementation in Semarang.